Breast Cancer Detective (Out of Print) - Marilyn Roubidoux (Association of American Medical Colleges, 2006)
Abstract This is an interactive computer tool for teaching breast imaging to fourth-year medical students. The web-based game allows for competitive play between two students, or between one student and one of two cyber players. Players compete to answer a series of case scenarios and questions. The game content was determined from a survey of faculty members in breast imaging. The preexisting knowledge of the content was tested with a quiz of 16 fourth-year medical students.